Hypomethylating drugs efficiently decrease cytosine methylation in telomeric DNA and activate telomerase without affecting telomere lengths in tobacco cells - Majerová, Eva; Fojtová, Miloslava; Mozgová, Iva; Bittová, Miroslava; Fajkus, Jiří (Plant molecular biology, 2011)
Telomere homeostasis is regulated at multiple levels, including the local chromatin structure of telomeres and subtelomeres. Recent reports demonstrated that a decrease in repressive chromatin marks, such as levels of cytosine methylation in subtelomeric regions, results in telomere elongation in mouse cells. Here we show that a considerable fraction of cytosines is methylated not only in subtelomeric, but also in telomeric DNA of tobacco BY-2 cells. Drug-induced hypomethylation (demonstrated at subtelomeric, telomeric, and global DNA levels) results in activation of telomerase. However, in contrast to mouse cells, the decrease in 5-methylcytosine levels and upregulation of telomerase do not result in any changes of telomere lengths. These results demonstrate the involvement of epigenetic mechanisms in the multilevel process of regulation of telomerase activity in plant cells and, at the same time, they indicate that changes in telomerase activity can be overridden by other factors governing telomere length stability.
Keywords: cytidin; DNA Methylation; tabák; Epigenesis, Genetic; epigeneze genetická; aktivace enzymů; Telomere; genetická transkripce; Nicotiana; Plant Proteins; DNA, Plant; metylace DNA; adenin; Cytidine; Adenine; telomery; Nucleosomes; Telomerase; kultivované buňky; Cells, Cultured; telomerasa; nukleozomy; DNA rostlinná; rostlinné proteiny; Transcription, Genetic; Enzyme Activation